IN-DEPTH ISLAMIC STUDY OF â€œRUMAH ISLAMIâ€ IN KELURAHAN SEI KERA HILIR I KECAMATAN MEDAN PERJUANGAN, MEDAN - Loebis, M. N.; Lindarto, D; Harisdani, D.D. (Talenta Publisher, 2018)
As implementation of Tri Dharma is a Community Services. This activity is carried out directly in the field by involving the public and university lecturers together in an effort to overcome the practical application of science in a comprehensive community issues. This community service focused on the in-depth problems of Islamic studies at the Serikat Amal Baik mosque in Kelurahan Sei Kera Hilir I, precisely on Jalan Ibrahim Umar Gg. Nikmat No. 7, Medan city. Working together with the partner Badan Kemakmuran Masjid (BKM) and teachers at SDIT Zahira school, conduct â€œRumah Islamiâ€ studies and perform continued of comfort supporting infrastructure improvement activities as part of the worship of Islam by Zahira SDIT teachers joining together the surrounding communities. This community service activities that have been carried out concluded that the targets and outcomes achieved by seeing the enthusiasm of the participants in the Islamic spiritual education development framework on an ongoing basis.